2005
DOI: 10.1111/j.1477-9730.2005.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

3D Building Modelling with Digital Map, Lidar Data and Video Image Sequences

Abstract: Three‐dimensional (3D) reconstruction and texture mapping of buildings or other man‐made objects are key aspects for 3D city landscapes. An effective coarse‐to‐fine approach for 3D building model generation and texture mapping based on digital photogrammetric techniques is proposed. Three video image sequences, two oblique views of building walls and one vertical view of building roofs, acquired by a digital video camera mounted on a helicopter, are used as input images. Lidar data and a coarse two‐dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…When all disk points are extracted, the reference points for the point clusters (an example of which is shown in Figure 7(a)) need to be determined to identify the centre coordinate for each disk. An alternative approach may be to use least squares template matching [55][56][57] or ellipse fitting [58] to determine corresponding GCP locations in multiple images and then compute 3D centre point coordinates in the arbitrary coordinate system based points in the cloud (found using cluster extraction) and their matched feature descriptor vectors (containing corresponding image coordinates). This has not been attempted here and is being considered for future studies.…”
Section: Uav-mvsmentioning
confidence: 99%
“…When all disk points are extracted, the reference points for the point clusters (an example of which is shown in Figure 7(a)) need to be determined to identify the centre coordinate for each disk. An alternative approach may be to use least squares template matching [55][56][57] or ellipse fitting [58] to determine corresponding GCP locations in multiple images and then compute 3D centre point coordinates in the arbitrary coordinate system based points in the cloud (found using cluster extraction) and their matched feature descriptor vectors (containing corresponding image coordinates). This has not been attempted here and is being considered for future studies.…”
Section: Uav-mvsmentioning
confidence: 99%
“…LiDAR has been exploited extensively in aerial reconstructions [10,15,19,22,23,24,25,38,39,40]. However, in sharp contrast to the proposed method, these methods assume that LiDAR provides a noise-free and accurate geometry, relegating images solely as a source of texture information and neglecting image-based geometric information.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Furthermore, an image sequence can be extracted from video to reconstruct a 3D geometric and texture model of a building efficiently. Zhang et al (2005) reported an approach for rapidly creating a textured 3D model of a building by combining helicopter-based video, Lidar data, and a 2D vector map. However, there were some limitations due to the helicopter-based video used.…”
Section: Introductionmentioning
confidence: 99%